The Octa Hand: An Affordable Multi-Grasping 3D-Printed Robotic Prosthesis for Transradial Amputees - Abarca V.E. (2019)
This work describes the development of a prosthesis hand prototype with an active wrist. The Octa Hand can perform at least six grasping shapes: rest, tip, tripod, power, spherical and extension. Cables and pulley mechanism was used on each finger to enable the flexion/extension and under-actuated abduction/adduction movement while worm drive and internal helical gear mechanisms were used on the wrist to enable the flexion/extension and pronation/supination movements. To obtain an anthropomorphic, compact, low-weight and low-cost result, the prototype was designed based on a CAD model using 3D scanner technology, and the prototype was manufactured with 3D printed technology with a total weight of 950g. A control algorithm was tested for speed and fingertips force evaluation of each degree of freedom and the force in the fingertips. As a result, the average speed of the fingers was 140 deg/s and the average force of each finger was 4.6N. © 2019 IEEE.